Hubungan Perilaku Konsumsi Dengan Status Gizi Remaja Putri Di Kabupaten Brebes - Suci Fitriana Pramudya Wardani; Siti Fatimah; Siti Nurafifah (Prosiding Seminar Nasional Ilmu Kesehatan dan Keperawatan, 2024)
Nutritional Problems In Adolescents Can Affect Cognitive Ability, Productivity, And Performance. The Impact Of Nutritional Problems Depends On Nutritional Status, I.E. Poor Nutritional Status Is At Risk Of Infectious Diseases While Nutritional Status Is Over And Obesity Is At Risk Of Experiencing Various Degenerative Diseases). Adolescent Behavior And Poor Food Quality Are The Main Causes Of Nutritional Problems. Disease Infection May Also Be The Cause Of Low Nutritional Status In Adolescents. The Purpose Of This Study Is To Determine The Relationship Between Consumption Behavior And The Nutritional Status Of Adolescent Girls At Al-Falah Sofwaniyah Jatirokeh Islamic Boarding School, Brebes Regency In 2023. This Research Method Uses Analytical Methods With A Cross-Sectional Approach Design, Then The Data Is Processed Using Tabulation. The Population In This Study Was Adolescent Girls In The Al-Falah Sofwaniyah Islamic Boarding School, Jatirokeh, Brebes Regency As Many As 40 Respondents Aged 10-15 Years. The Sample In This Study Was 40 Respondents With Total Sampling Technique. This Research Place Was Carried Out At The Al-Falah Sofwaniyah Islamic Boarding School, Brebes Regency In 2023. This Research Has Been Conducted On November 23 – December 15, 2023. The Tool Used In This Study Was A Questionnaire. Analyze Data Using Chi-Square. The Results Of This Study Show That There Is No Relationship Between Consumption Behavior And The Nutritional Status Of Adolescent Girls At The Al-Falah Sofwaniyah Jatirokeh Islamic Boarding School, Brebes Regency 2023 With A Value Of P = 0.108. There Is No Relationship Between Consumption Behavior And The Nutritional Status Of Adolescent Girls At The Al-Falah Sofwaniyah Islamic Boarding School, Jatirokeh, Brebes Regency 2023. Efforts To Improve The Nutritional Status Of Adolescents Can Be Made By Providing Education About Nutrition Efforts To Improve The Nutritional Status Of Adolescents Can Be Made By Providing Education About Nutrition So That They Can Change Eating Behavior And Physical Activity To Improve Their Health Status.